Effect of Viral Double-Stranded RNA on Mammalian Cells in Culture: Cytotoxicity Under Conditions Preventing Viral Replication and Protein Synthesis - Cordell-Stewart, B. (1973)
Noninfectious bovine enterovirus double-stranded RNA induces cytopathic effects when added to mammalian cells in culture. This is demonstrated by (51)Cr release from prelabeled murine lymphoma cells and trypan blue uptake. Also, the induction of cell death by this viral RNA occurs in the presence of inhibitors of protein synthesis (cycloheximide and puromycin). The possible role and mechanism of viral, double-stranded RNA as a cytopathic agent in virally infected cells are discussed.